Low availability of haematin (hemin) in Pakistan - Fatima Ahsan; Muhammed Ifham Mohamed Imtiyas; Abdul Raheem Rizvie (Journal of the Pakistan Medical Association)
Madam, Acute Intermittent Porphyria (AIP) is an autosomal dominant disorder that results from a defect in the enzyme named porphobilinogen deaminase.1 It is symptomatic porphyria, involving the accumulation of porphyrins and porphyrin precursors due to impaired conversion in haeme synthesis. Acute Intermittent Porphyria is clinically characterized by acute episodes of multiple gastrointestinal and neurologic symptoms; during which the patient remains healthy between episodes.2 Acute Intermittent Porphyria episodes are commonly observed in post pubertal females. The most common symptoms include periodic abdominal pain, vomiting and hypertension followed by neurologic damage that leads to peripheral and autonomic neuropathies (mostly motor) and psychiatric manifestations.2 Hormonal cycle regulation may worsen porphyria, since its symptoms coincide with the menstrual cycle. Although positive response has been noted in hormonal suppression by gonadotropin releasing hormone agonists.3